(untitled) (Human Factors in Design, 2012)
This article gives examples on how to use knowledge related to human abilities on the development of a hierarchy of users’ request, helping and guiding an ergonomic project. The article presents different methods of classification of the human abilities and exemplifies with a tool that correlates aged users’ requests with the abilities needed to interact with automatic teller machines of banks.